Christoph Berner - Manuel Schäfer – Martin Schott – Sarah Shulz – Martina Weingärtner (eds.), Clothing and Nudity in the Hebrew Bible (T&T Clark: London – New York – Oxford 2019) - Rambiert-Kwaśniewska, Anna (The Biblical Annals, 2020)
Book Review: Christoph Berner - Manuel Schäfer – Martin Schott – Sarah Shulz – Martina Weingärtner (eds.), Clothing and Nudity in the Hebrew Bible (T&T Clarc: London – New York – Oxford 2019)